2009
DOI: 10.1038/nm.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the Toll-like receptor–mediated response of plasmacytoid dendritic cells to HIV-1

Abstract: Manifestations of viral infections can differ between women and men 1 , and significant sex differences have been described in the course of HIV-1 disease. HIV-1-infected women tend to have lower viral load levels early in HIV-1 infection, but progress faster to AIDS for a given viral load than men 2-7 . Here we demonstrate substantial sex differences in the response of plasmacytoid dendritic cells (pDCs) to HIV-1. pDCs derived from women produce significantly more interferon-α (IFN-α) in response to HIV-1-enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
474
7
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 520 publications
(521 citation statements)
references
References 38 publications
32
474
7
8
Order By: Relevance
“…Our data adds to previous reports on the influence of sex on production of IFNα by pDCs, demonstrating that also surface maturation markers are upregulated more in female pDCs (Berghöfer et al, 2006;Meier et al, 2009;Seillet et al, 2012Seillet et al, , 2013. The effect of sex on upregulation of especially CD40 but also CD86 was respectively mostly or partially explained by the rs179008 variant allele.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our data adds to previous reports on the influence of sex on production of IFNα by pDCs, demonstrating that also surface maturation markers are upregulated more in female pDCs (Berghöfer et al, 2006;Meier et al, 2009;Seillet et al, 2012Seillet et al, , 2013. The effect of sex on upregulation of especially CD40 but also CD86 was respectively mostly or partially explained by the rs179008 variant allele.…”
Section: Discussionsupporting
confidence: 74%
“…For HBV, the prevalence of the variant allele among chronic patients has not yet been explored. pDC function is also affected by sex: male pDCs, as compared to female pDCs, produce less IFNα upon TLR7 but not TLR9 ligation (Berghöfer et al, 2006;Meier et al, 2009). This difference is believed to derive from expression differences of X-chromosomal genes downstream of TLR7, combined with hormonal effects (Seillet et al, 2012(Seillet et al, , 2013Griesbeck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…20 Therefore, type I IFN levels are likely to play a role in the pathogenesis of AIDS during HIV or SIV infection. 23 Meier et al 24 reported the difference in the rate of AIDS progression between male and female HIV-positive patients correlated with level of IFN-a, as the PBMCs derived from female patients produced higher levels of IFN-a in response to TLR7 ligands than those derived from male patients. It was also reported that circulating pDCs in HIVinfected individuals showed an increase in IFN-a expression.…”
Section: Discussionmentioning
confidence: 99%
“…Work from Dr. Marcus Altfeld's laboratory has shown a gender difference in the profile of interferon production, with HIV-mediated interferon induction much higher in women compared to men. 51 Women also have higher immune activation than men, which increases through reproductive aging. 52 Many of the clinical aspects associated with aging appear to be accelerated in ART-treated HIV-infected adults.…”
Section: Biomarkers For Immune Activationmentioning
confidence: 99%